Probing triplex formation by EPR spectroscopy using a newly synthesized spin label for oligonucleotides - Gannett, Peter M. (Oxford University Press, 2002)
Spin labels have been extensively used to study the dynamics of oligonucleotides. Spin labels that are more rigidly attached to a base in an oligonucleotide experience much larger changes in their range of motion than those that are loosely tethered. Thus, their electron paramagnetic resonance spectra show larger changes in response to differences in the mobility of the oligonucleotides to which they are attached. An example of this is 5-(2,2,5,5-tetramethyl-3-ethynylpyrrolidine-1-oxyl)-uridine (1). How ever, the synthesis of this modified DNA base is quite involved and, here, we report the synthesis of a new spin-labeled DNA base, 5-(2,2,6,6-tetramethyl-4-ethynylpiperidyl-3-ene-1-oxyl)-uridine (2). This spin label is readily prepared in half the number of steps required for 1, and yet behaves in a spectroscopically analogous manner to 1 in oligonucleotides. Finally, it is shown here that both spin labels 1 and 2 can be used to detect the formation of both double-stranded and triplex DNA.